Qur'an and Climate Change - Beni, Abdolmajid Naderi (Universitas Muhammadiyah Surakarta, 2024)
Climate change is a serious issue that we must face. It requires action that goes beyond just scientific methods and includes insights from religious teachings. The Holy Qur'an, which often mentions weather and climate, hasn't been fully explored by religious scholars in this area. These texts show weather as a sign of God's power, and as a way to show kindness or punishment. This study suggests a fresh examination of the Qur'an's climate-related stories, looking for links with past weather events and God's messages. It argues that Islamic principles could help us address the climate crisis and encourages religious scholars to apply these ideas to current environmental issues. By examining the Qur'an's descriptions of climate across different regions and times, we aim to connect ancient warnings with today's scientific understanding. The paper calls for a combined approach, where religious perspectives enhance scientific research, leading to a sustainable way of living.